2023
DOI: 10.3389/fmicb.2023.1290246
|View full text |Cite
|
Sign up to set email alerts
|

The causality between gut microbiome and anorexia nervosa: a Mendelian randomization analysis

Xuan Xia,
Shu-yang He,
Xiao-Lin Zhang
et al.

Abstract: Background and aimNutrient production by intestinal microbiota corresponds to regulate appetite while gut microbial composition was influenced by diet ingestion. However, the causal relationship between gut microbial taxa and anorexia nervosa (AN) remains unclear. Mendelian Randomization (MR) is a novel research method that effectively eliminates the interference of confounding factors and allows for the exploration of the direct causal effects between exposure and outcome. This study employs MR to explore the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
4
1
Order By: Relevance
“…In a previously published MR analysis, Actinobacteria , Bilophila , Holdemania , Lactobacillus , Ruminococcaceae UCG009 , and two unknown gut microbes were identified as risk factors for the development of AN, which is very different from our conclusions ( Xia et al, 2023 ). Interestingly, the results are highly similar to those of our BN study.…”
Section: Discussioncontrasting
confidence: 99%
“…In a previously published MR analysis, Actinobacteria , Bilophila , Holdemania , Lactobacillus , Ruminococcaceae UCG009 , and two unknown gut microbes were identified as risk factors for the development of AN, which is very different from our conclusions ( Xia et al, 2023 ). Interestingly, the results are highly similar to those of our BN study.…”
Section: Discussioncontrasting
confidence: 99%
“…Their findings indicate that certain microbial taxa, including Actinibacteria , Bilophila , Holdemania , Lactobacillus , and Ruminococcaceae , function as risk factors for the occurrence of AN, while others such as Eubacteriumnodatum and Melaina bacteria act as protective factors. Furthermore, the investigation into the impact of AN on the gut microbiome revealed that the abundance of Alphaproteobacteria , Coriobacteriaceae , Christensenellaceae , and Anaerostipes species is influenced by the presence of AN [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to a previous longitudinal study, individuals with AN possess substantially great abundances of Alistipes, Clostridiales, Christensenellaceae, and Ruminococcaceae and a lower abundance of Faecalibacterium, Agathobacter, Bacteroides, Blautia, and Lachnospira (84). A recent MR study revealed that AN was associated with increased levels of gut microbiome, including Alphaproteobacteria, Christensenellaceae, and Coriobacteriia (103). Variations in the gut microbiome make a person more prone to sepsis because they promote the growth of harmful bacteria in the gastrointestinal tract and trigger a robust proinflammatory response in the immune system (85).…”
Section: Discussionmentioning
confidence: 99%